الشباب ومشكلة وقت الفراغ – بحث ميداني في مدينة بغداد منطقتي الكرخ والرصافة أنموذجاً - يوسف قنبر فراس (Al-Adab Journal, 2018)
The goal of research is to identify how to investment leisure time among young people , and to identify the most important reasons young people feeling free time , search find studied your free time when young people the youth male of humanitarian and scientific college students totaling (100) students distributors scientific and humanitarian college . The importance of the subject free time it touches an important segment within the social organization have a responsibility to carry pressure in the future it is at same time a key goal of sustainable development . where there is a correct way her results with positive returns, but if the basic elements did not have thy will reflect on their social performance .search come up a problem through leisure time on youth as it known to be divided into two parts time work or study time and work time . and lack of interest by the it would kill the spirit of creativity among young people it does not allow for the mental and physical abilities to emerge .The importance of research come through the study of the main category within the social organization of a youth through which can identify strengths and weaknesses in the social structure .from here the idea of attention appeared leisure as posing a risk to young people especially in the absence of the means of social control and poor oversight with a family with a bad companionship and young people affected by the cultures contained . While the goal of research for the detection of